2022
DOI: 10.3390/ijerph19126989
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parent–Child Attachment on School Adjustment in Left-behind Children Due to Transnational Parenting: The Mediating Role of Peer Relationships

Abstract: In China’s eastern coastal areas, the transnational parenting of left-behind children creates a distinct form of left-behind child. Previous research has indicated that children who have been left behind have a low degree of school adjustment. The major purpose of this research was to investigate the impact of parent–child attachment on school adjustment in children left behind by migrant parents, as well as the mediating role of peer relationships in this process. The parent–child attachment section of the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These negative childhood experiences can further increase a child’s withdrawal behaviors and rejection of peer interactions, resulting in a withdrawn personality disorder ( Guina, 2016 ; Bang et al, 2018 ). There is a strong correlation between children’s emotion management and well-being and parenting styles and children’s peer interactions ( Malonda et al, 2019 ; Zhang and Deng, 2022 ). Therefore, we hypothesized that parenting styles may be predictors of peer interactions, such that authoritarian parenting styles negatively predict peer interactions, whereas authoritative parenting styles positively predict peer interactions.…”
Section: Introductionmentioning
confidence: 99%
“…These negative childhood experiences can further increase a child’s withdrawal behaviors and rejection of peer interactions, resulting in a withdrawn personality disorder ( Guina, 2016 ; Bang et al, 2018 ). There is a strong correlation between children’s emotion management and well-being and parenting styles and children’s peer interactions ( Malonda et al, 2019 ; Zhang and Deng, 2022 ). Therefore, we hypothesized that parenting styles may be predictors of peer interactions, such that authoritarian parenting styles negatively predict peer interactions, whereas authoritative parenting styles positively predict peer interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the relationship between parent–child attachment and school adjustment was even more pronounced among children left behind by overseas parents, where the isolation of children from their parents—the “defining characteristic” of such children—is the core indicator that distinguishes children left behind from those not left behind ( Chung et al, 2021 ). Children separated from their parents for sustained periods demonstrate significantly lower levels of parent–child attachment than those who remain together ( Zhang and Deng, 2022 ), and relatively lower levels of school adjustment, pointing to the developmental risks to left-behind children ( Doumen et al, 2012 ). Interventions might therefore center on improving parent–child attachment as a means of enhancing left-behind children’s adjustment to their schools, such as improving the quality of parent–child communication ( Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…No studies, however, have looked at the presence of multiple psychological resources (such as hope and gratitude) and how they interact in reducing the adverse effects of NLEs on school adjustment in samples of Chinese adolescents who were left-behind. Fewer studies [ 8 , 36 ] have examined how these adolescents adjust to school. The current study aims to comprehend the underlying mechanisms relating NLEs to school adjustment among Chinese left-behind students.…”
Section: Current Studymentioning
confidence: 99%
“…Researchers have found that these adolescents are at a crucial stage of mental development and their mental health is often more affected than their physical health [ 6 ]. Despite parents' migration to support their education, left-behind adolescents often struggle with school adjustment and are more prone to academic and behavioral issues [ 7 , 8 ]. Lam and Yeoh [ 9 ] suggest that their poor school performance may be attributed to unstable home environments, insufficient parental care, and a lack of mental health education in their schools.…”
Section: Introductionmentioning
confidence: 99%